(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper, the existence theorem for the first order functional differential equations in Banach algebras is seen under the mixed generalized conditions of Lipschitz and Caratheodory. The presence of Extremal solutions is also proven under such monotonicity conditions.